Effect of Bisoctrizole on Ultraviolet (UV) Absorption Properties of Silicone and Effect on Surface Roughness - An In Vitro Study - Widyan Abbas Ahmed; Bayan Saleem Khalaf (Wolters Kluwer Medknow Publications, 2024)
Background Premature degradation is the problem of maxillofacial silicones, significantly affected by ultraviolet exposure, contributing to silicones photodegradation. Degradation necessitates frequent replacement of prostheses that increase the total cost of rehabilitation. Aims This study evaluated the effect of bisoctrizole on the ultraviolet absorption properties of silicone material and the stability of this absorption over time. Also, the bisoctrizole effect on the surface roughness of silicone was evaluated. Methods There were 60 prepared specimens of room temperature-vulcanising maxillofacial silicone equally divided into two groups according to the conducted tests: ultraviolet absorption test and the surface roughness test. Each group was further subdivided into groups of 10 specimens based on the weight concentration of the ultraviolet (UV) absorber added: 0%, 1% and 2%. The UV absorbance of coloured specimens was measured before and after artificial weathering for 100 and 200 hours. Repeated-measures analysis of variance (ANOVA) was applied for UV absorption results, and one-way ANOVA was applied for the roughness test results to test the changing significances. Result Bisoctrizole incorporation led to a highly significant improvement in ultraviolet absorption in all groups, maintaining a high level even after subjecting the specimens to artificial weathering. Furthermore, the addition resulted in a significant increase in surface roughness as the concentration of bisoctrizole increased. Conclusion Despite the surface roughness changes, bisoctrizole demonstrated efficacy as a UV absorber for maxillofacial silicone, making it valuable for applications such as maxillofacial prosthetics that require UV protection.